PROBLEMS OF LEGAL PROTECTION OF SEMICONDUCTOR PRODUCT ASSEMBLY IN UKRAINE - Muzyka, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to clarify the main problems of legal protection of the composition of semiconductor products as an object of intellectual property law, to highlight the differences in the legal protection of the right of intellectual property for the composition of semiconductor products, provided for in national legislation and the Association Agreement between Ukraine and the European Union, and as well as an analysis of the legislation regulating the protection of the right to assemble semiconductor products in Ukraine, scientific concepts on this issue and the experience of foreign countries in order to find ways to improve the current national legislation regulating the specified relations. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to identify and describe the problems of legal protection of the composition of semiconductor products in Ukraine. Results: a significant number of provisions of the Association Agreement between Ukraine, on the one hand, and the European Union, the European Atomic Energy Community and their member states, on the other hand, require their implementation at the level of codified regulation, as by amending Book 4 of the Civil Code of Ukraine, as well as by improving special legislation on the protection of intellectual property rights for the composition of semiconductor products as separate objects of intellectual property rights. The specified changes should refer directly to the provisions of the special Law of Ukraine "On Protection of Rights to the Composition of Semiconductor Products": assignment of specifically defined coded information to the protected right, full and objective verification of the set of elements (methods, system, technology and coded information) for originality. Discussion: the systematic analysis of the researched question shows the obvious problematic of the scope of legal protection of the composition of semiconductor products (topologies of integrated circuits) in Ukraine, because it is limited only by state registration and the refusal to check the set of elements (methods, systems, technology and coded information) for originality, and also the restriction (prohibition) on assigning coded information to legal protection is a consequence of incomplete and not comprehensive verification of the conditions of protection and its effectiveness in the field of intellectual property law. According to world practice, legal protection should provide for appropriate sanctions for violation of the right to a protected object of intellectual property, and not just state registration. Accordingly, legal protection is granted only to the registered intellectual property right for the layout of semiconductor products (integrated microcircuit topology) without prior analysis and makes the author dependent on the actions of others, that is, burdens the latter on his own verification of the registration of similar products in the world.